2012
DOI: 10.1177/1403494811435487
|View full text |Cite
|
Sign up to set email alerts
|

Danish heart patients’ participation in and experience with rehabilitation

Abstract: Few Danish patients with ischaemic heart disease participate in a complete rehabilitation programme mainly due to psychosocial elements not yet being an integral part of cardiac rehabilitation in Denmark. There is a need to differentiate and tailor cardiac rehabilitation to different patient segments, e.g. by gender and age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 6 publications
0
14
2
1
Order By: Relevance
“…Previous studies reported that women and younger clients tended to report lower satisfaction scores with the services 2830. The relatively small sample in the present study might have prevented the detection of statistically significant difference.…”
Section: Discussioncontrasting
confidence: 64%
“…Previous studies reported that women and younger clients tended to report lower satisfaction scores with the services 2830. The relatively small sample in the present study might have prevented the detection of statistically significant difference.…”
Section: Discussioncontrasting
confidence: 64%
“…On the other hand, gender seems to have impact on satisfaction with life in patients with coronary heart disease, where men report increased well‐being after the initial hospitalization (25). Also, among men with coronary heart disease men were more satisfied than women with their rehabilitation (26), contrary to our findings among patients with stroke.…”
Section: Discussioncontrasting
confidence: 99%
“…An observational study from Israel indicated more frequent return to the workforce among participants in a cardiac rehabilitation programmes, in a population with a participation rate at 7% [12]. In Denmark complete participation in cardiac rehabilitation has been found even lower for patients with ischaemic heart disease [24]. More knowledge regarding the impact of cardiac rehabilitation on the possibility to return to the workforce is needed among patients who undergo cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%